IMPLICATION OF INTERNSHIP III PROGRAMS ON SOCIAL COMPETENCY OF PENMAS STUDENTS OF IKIP SILIWANGI - Wedi Fitriana; Dinno Mulyono (Jurnal Ilmiah P2M STKIP Siliwangi, 2019)
The apprenticeship program III is one of the academic agendas in developing student competencies, so that they are ready to undergo the profession as community educators. However, based on the identification of problems carried out internally, it was found that the apprenticeship program III, had not provided optimal results, this can be seen from the results of evaluations and feedback from the people who were targeted in the apprenticeship program III of the IKIP Siliwangi Community Education study program. The theoretical foundation used in this study is the theory of learning through practice, the theory of social competence and the theory of public education. The research method used is descriptive qualitative with the instruments used are interview guides, guidelines for observation and documentation study. The results obtained that the competence of students in the public education study program showed an increase especially in terms of communication and social interaction skills. However, it has not received a good assessment from the community. So that the conclusions in this study are that the internship program III has positive implications for the development and social competence of students, but still needs further development.